The literature of immigration and racial formation : becoming white, becoming other, becoming American in the late Progressive Era - Brown, Linda Joyce, 1967- (American popular history and culture (Routledge (Firm)), 2004)
This work examines early twentieth-century literature about women immigrants in order to reveal the differing ways that American racial categories and identities, particularly that of whiteness, were textually and socially constructed at the beginning of the twentieth century.